2020
DOI: 10.1242/jeb.222893
|View full text |Cite
|
Sign up to set email alerts
|

Mussels' acclimatization to high, variable temperatures is lost slowly upon transfer to benign conditions

Abstract: Climate change is increasing the temperature variability animals face, and thermal acclimatization allows animals to adjust adaptively to this variability. Although the rate of heat acclimatization has received some study, little is known about how long these adaptive changes remain without continuing exposure to heat stress. This study explored the rate at which field acclimatization states are lost when temperature variability is minimized during constant submersion. California mussels (Mytilus californianus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 63 publications
1
23
2
1
Order By: Relevance
“…Species inhabiting intertidal zones must have high tolerance for environmental changes, as they are continuously exposed to fluctuation of ambient conditions, including temperature and salinity (Gosling 2003;Gracey et al 2008). Various studies have investigated physiological adaptations to temperature changes and their impact on species distributions (Pernet et al 2007;Tomanek and Zuzow 2010;Somero 2012;Seuront et al 2019;Moyen et al 2020;Chao et al 2020;Popovic and Riginos 2020). Mechanisms of osmotic adaptation have also been studied, through physiological, transcriptomic and proteomic, and behavioral analyses (Gosling 2003;Lockwood and Somero 2011;Tomanek et al 2012;Wang et al 2013).…”
Section: Environmental Adaptations Of Intertidal Musselsmentioning
confidence: 99%
“…Species inhabiting intertidal zones must have high tolerance for environmental changes, as they are continuously exposed to fluctuation of ambient conditions, including temperature and salinity (Gosling 2003;Gracey et al 2008). Various studies have investigated physiological adaptations to temperature changes and their impact on species distributions (Pernet et al 2007;Tomanek and Zuzow 2010;Somero 2012;Seuront et al 2019;Moyen et al 2020;Chao et al 2020;Popovic and Riginos 2020). Mechanisms of osmotic adaptation have also been studied, through physiological, transcriptomic and proteomic, and behavioral analyses (Gosling 2003;Lockwood and Somero 2011;Tomanek et al 2012;Wang et al 2013).…”
Section: Environmental Adaptations Of Intertidal Musselsmentioning
confidence: 99%
“…physiological plasticity) compared to more mobile animals as a result of their inability to behaviourally thermoregulate [5]. Previous research in mussels has found that physiological changes in the initial stages of heat acclimation predominantly occur within the nervous system [9,45], whereas longer-term changes that occur with heat acclimation typically involve cellular, cardiovascular, respiratory, and metabolic changes (or other organ systems that have been largely unexplored to this point) [14,15,19,28,36,41,46,47]. Regardless of the sequence with which these physiological changes occur, it seems that the physiological changes that conferred long-lasting heat tolerance (from this sublethal heat bout) were maximized at 2 and 5 days after the 30 and 35°C heat-stress bouts, respectively, as this is when survival peaked in each group (figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…flatline temperature, mean ± s.d. = 40.4 ± 1.3°C; [36]). Moreover, through a pilot study using control mussels that were not subjected to any sublethal heat-stress bout, 2 h at 40°C led to approximately 75-90% mortality within three to four weeks (data not shown).…”
Section: (A) Survival Testsmentioning
confidence: 96%
“…To those who have contributed so much insight through studies of cardiac function (Caren Braby, Emily Stenseng, Jonathon Stillman, Nishad Jayasundara, Carolyn Tepolt, and Nicole Moyen), I offer my warmest appreciation and my sincere apologies for not finding a way to fit in even a short summary of all that you've done. Readers wishing to learn these fascinating stories about the heart should check out several key papers (Stillman & Somero 1996, 2000Braby & Somero 2006;Jayasundara et al 2013;Tepolt & Somero 2014;Moyen et al 2019Moyen et al , 2020). It's especially frustrating to me that the work on depth-related metabolic biochemistry and the molecular basis of metabolic scaling done with my close friend Jim Childress couldn't be shoehorned into this review (Childress & Somero 1979, Somero & Childress 1980, Torres & Somero 1988.…”
Section: What You Aren't Going To Read Aboutmentioning
confidence: 99%